Understanding Self‐Perceived and Other‐Perceived Body Image in Adolescents: The Roles of Neuroticism, Mindfulness, and Self‐Compassion - An, Yuening; Lu, Aitao; Chen, Guoping; Jian, Yexuan; Chen, Wanyi; Ke, Xiayao; Zhong, Yingjie; Li, Jiayi (Psychology in the schools, 2025)
ABSTRACT This study explored the intricate dynamics between neuroticism and body image among adolescents, focusing on the mediating roles of mindfulness and self‐compassion. We also differentiate between self‐perceived body image—how individuals view their own bodies—and other‐perceived body image—how they perceive others view their bodies. Participants were recruited from a random sample of high school students in Chaozhou of Guangdong Province (China) (N = 937, Mage = 14.15 years, SD = 0.90, 476 girls). They completed questionnaires assessing neuroticism, mindfulness, self‐compassion, self‐perceived body image, and other‐perceived body image. Serial mediation regression models manifested that the relationship between neuroticism and body image was significantly mediated by mindfulness and self‐compassion. Specifically, neuroticism was negatively related to self‐perceived body image through its negative relationships with mindfulness, self‐compassion, and other‐perceived body image. The findings highlight the importance of addressing both internal attitudes and social factors in promoting a positive body image among adolescents. Summary Neuroticism was negatively associated with self‐perceived body image. Mindfulness and self‐compassion completely mediated the association between neuroticism and self‐perceived body image or other‐perceived body image. Other‐perceived body image mediated the association between neuroticism and self‐perceived body image in a creative way.